Structural and Stratigraphic Study of the Nahr Umr Formation (Lower Cretaceous) Using 3D seismic Survey in Abu Amood Oil Filed, Southern Iraq - Z.Khorshid, Salman; Z.Khorshid, Salman; I. Khaleel, Ahmed (Iraqi Journal of Science, 2021)
3D seismic reflection study was applied to Abu Amood oil field which is located at the southern part of Iraq within DhiQar province that carried out by oil Exploration Company to an area of 1534.88 Km2 for studying Nahr Umr Formation. Synthetic seismogram was prepared by using available data of well (AAM-1) in order to define and picking the reflectors on the seismic section. These reflectors are (Top of Nahr Umr Formation and middle unit of Nahr Umr Formation which represents the layer of sand). The seismic section time slice maps confirmed that the Nahr Umr Formation was not affected by faults and the faults may probably present in the Ratawai and Yamama Formations, where the variance attribute applied on seismic sections showed that the area was affected by normal fault, this fault was very deep. The time, velocity, and depth maps are drawn for the top of Nahr Umr Formation to get the structural picture: these maps showed that Abu Amood oil field was a semi symmetrical structure that has an axis trending NW-SE, the slope of NE limb is greater than SW limb. Isochrone and Isopach maps are drawn for Nahr Umr Formation to display thickness of Nahr Umr Formation which gradually increases to the west as well as NW and SW parts of the study area and more gradually increases to the East and NE part of the study area. Seismic attributes were applied to the study area (instantaneous phase, instantaneous frequency and variance attribute) these attributes showed the presence of Direct Hydrocarbone Indicator at Nahr Umr Formation in Lower Cretaceous age as a Dim spot at In-lines 51500 and 49500 by applying instantaneous phase and bright spot at AAM-1 well by applying instantaneous frequency.